Use of isotopic sulfur to determine whitebark pine consumption by Yellowstone bears: A reassessment - Charles C. Schwartz; Justin E. Teisberg; Jennifer K. Fortin; Mark A. Haroldson; Christopher Servheen; Charles T. Robbins; Frank T. van Manen (Wildlife Society Bulletin)
ABSTRACT Use of naturally occurring stable isotopes to estimate assimilated diet of bears is one of the single greatest breakthroughs in nutritional ecology during the past 20 years. Previous research in the Greater Yellowstone Ecosystem (GYE), USA, established a positive relationship between the stable isotope of sulfur (δ34S) and consumption of whitebark pine (Pinus albicaulis) seeds. That work combined a limited sample of hair, blood clots, and serum. Here we use a much larger sample to reassess those findings. We contrasted δ34S values in spring hair and serum with abundance of seeds of whitebark pine in samples collected from grizzly (Ursus arctos) and American black bears (U. americanus) in the GYE during 2000–2010. Although we found a positive relationship between δ34S values in spring hair and pine seed abundance for grizzly bears, the coefficients of determination were small (R2 ≤ 0.097); we failed to find a similar relationship with black bears. Values of δ34S in spring hair were larger in black bears and δ34S values in serum of grizzly bears were lowest in September and October, a time when we expect δ34S to peak if whitebark pine seeds were the sole source of high δ34S. The relationship between δ34S in bear tissue and the consumption of whitebark pine seeds, as originally reported, may not be as clean a method as proposed. Data we present here suggest other foods have high values of δ34S, and there is spatial heterogeneity affecting the δ34S values in whitebark pine, which must be addressed. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.